Deconstructing Anthropocentrism: A Posthumanist Reading of Mulk Raj Anand’s The Parrot in the Cage - Joshi, Deepak (Far Western Review, 2024)
This article examines the deconstruction of anthropocentrism in Mulk Raj Anand’s The Parrot in the Cage through a Posthumanist perspective. Drawing on the theoretical insights of Charles Darwin, Jacques Derrida and Giorgio Agamben, this paper interrogates the conventional human/nonhuman dichotomy and advocates for a symbiotic relationship between them. Humans and nonhuman beings are often positioned in conflicting relationships, leading to domination, exploitation, consumption, and even extinction. From wild to tamed, aquatic to terrestrial, small to large, and strong to weak, nonhuman beings are compelled to exist in a state of perpetual defense, while humans, by contrast, exert aggressive control over them. The notion that humans possess inherent privileges over nonhuman entities is a construct of human culture, and the ongoing struggle between them emerges as a self-destructive conflict. Since all organisms rely on interdependent relationships for survival, symbiosis becomes an ecological and ethical necessity. This study, therefore, highlights the inherent proximity between humans and nonhumans despite their differences and advocates for a reconceptualization of their relationship. By re-examining and redrawing the boundaries between human and animal nature, the article seeks to foster a more sustainable and non-hierarchical understanding of life forms.